Indium Triflate Catalyzed Michael Addition of Amines to a,?-Unsaturated Esters and Nitriles: Synthesis of ?-Amino Esters and Nitriles - Thirupathaiah, A.; Venkateshwar Rao, G. (Asian Journal of Chemistry, 2010)
Amine undergoes Michael addition with α,β-unsaturated esters and nitriles to form β-amino esters and nitriles in excellent yields under mild conditions